Mycobacterium avium subsp. paratuberculosis antigens induce cellular immune responses in cattle without causing reactivity to tuberculin in the tuberculosis skin test - Gupta, Sandeep K.; Wilson, Tania; Maclean, Paul H.; Rehm, Bernd H. A.; Heiser, Axel; Buddle, Bryce M.; Wedlock, D. Neil (Frontiers in Immunology, 2023)
Updated abstract provided in the revised manuscript.